Associated Vulva Hygiene And Contraception Utilization With Leucorrhoea In Bearchild Age Women - aida Fitria; Mayang Wulan; Nurlela Br Ginting (Universitas Islam Jember, 2023)
According to WHO about 75% of women in the world will definitely experience vaginal discharge at least once in their lifetime, and around 45% will experience vaginal discharge twice or more. The purpose of this study was to determine the relationship of Vulva Hygiene and the use of contraception with vaginal discharge in women of BA women at Pratama Ananda Clinic in Medan in 2019. This type of research used an analytic survey, with a cross-sectional approach, the population in this study were all BA women and the samples were taken using accidental sampling technique amounted 38 respondents. data Analysis used Univariate and Bivariate Analyses to prove the correlation between the independent and dependent variables with the chi-square test. Results of the study were tested using chi-square obtained Vulva Hygiene results with p-value (.008) < (.05) and contraception use with p-value (.032) < (.05). This study is that there is a relationship between Vulva Hygiene and Use of contraception with Leucorrhoea in BA Women in Ananda Clinic, Medan.